Plasma cell-free DNA methylation marks for episodic memory impairment: a pilot twin study - M. Konki; N. Lindgren; M. Kyläniemi; R. Venho; E. Laajala; B. Ghimire; R. Lahesmaa; J. Kaprio; J. O. Rinne; R. J. Lund (Nature, 2022)
Decline in episodic memory performance usually causes the first clinical symptoms of Alzheimer’s disease. At present, Alzheimer’s disease can only be diagnosed at a very late stage when neurodegeneration and cognitive impairment is already irreversible. New early disease markers are needed for earlier and more efficient Alzheimer’s disease intervention. To identify early disease markers, we implemented a genome-wide bisulphite sequencing method for the analysis of plasma cell-free DNA methylation profiles and compared differences associated with episodic memory performance in Finnish twin pairs. A noticeable amount of cell-free DNA was present in plasma, however, the amounts as well as the genomic coverage of these fragments varied substantially between individuals. We found no significant markers associated with episodic memory performance in the twins’ plasma cell-free DNA methylation profiles. Furthermore, our results indicate that due to the low genomic coverage of cell-free DNA fragments and the variety in these fragments between individuals, the implemented genome-wide bisulphite sequencing method is not optimal for comparing cell-free DNA methylation differences between large groups of individuals.